Digital Literacy Mediates Hospital Information System Implementation Through Perceived Usefulness and Perceived Ease of Use - Ellisa Diana; Erry Yudhya Mulyani; Ratna Indrawati (International Forum of Researchers and Lecturers, 2026)
The implementation of Hospital Information Systems (HIS) has become a strategic priority for healthcare organizations seeking to improve service quality, operational efficiency, and clinical decision-making. Despite substantial investments in digital health technologies, many hospitals continue to encounter challenges in achieving effective HIS implementation due to differences in users’ perceptions of system usefulness, ease of use, and digital competencies. Understanding these factors is essential to ensure successful adoption and sustainable utilization of hospital information systems. This study aimed to examine the effects of Perceived Usefulness and Perceived Ease of Use on Hospital Information System implementation, with Digital Literacy serving as an intervening variable. A quantitative study with a cross-sectional design was conducted among 154 healthcare professionals who actively used the Hospital Information System at RSU Pekerja, Jakarta. Data were collected using a structured questionnaire and analyzed through Structural Equation Modeling (SEM) with AMOS software to evaluate both direct and indirect relationships among the study variables. The results demonstrated that Perceived Usefulness and Perceived Ease of Use significantly influenced Digital Literacy and Hospital Information System implementation. Digital Literacy also had a significant positive effect on system implementation and partially mediated the relationships between Perceived Usefulness and implementation, as well as between Perceived Ease of Use and implementation. The structural model explained 61.6% of the variance in Hospital Information System implementation (R² = 0.616), indicating satisfactory explanatory power. These findings highlight that enhancing users’ digital literacy strengthens technology acceptance and contributes to more effective implementation of hospital information systems. Hospitals should therefore invest in continuous digital literacy training, user-centered system development, and organizational support to optimize the adoption and long-term sustainability of digital health information systems.